Aplicações da função logarítmica em sala de aula no ensino médio: uma proposta de solução de problemas pela transposição para a linguagem matemática - Motoki, Marcia Eiko [UNESP] (2016)
Logarithms were created in the first half of the seventeenth century, to facilitate the mathematics becoming an efficient calculation tool, it has become a fundamental property products sum. Currently, even with the use of modern calculators available to all, its importance is no less than in the past, because it is related to various natural phenomena. Despite several applications in addition to the Financial Mathematics (simple and continuous interest) there are also applications in physics, chemistry, biology, geography and music. In my professional experience, solve problems involving logarithms is considered complicated by many students who do not understand its concept nor its usefulness. This work is an approach to solving problem situations involving logarithms, through a resolution scheme that explores the details of the statement by organizing relevant data, transposed into mathematical language and development of calculations to the final answer. To achieve this goal, it is made a revision of emergence of logarithms, the concept of empowerment, exponential function, logarithm as area and logarithmic function. Moreover, the logarithm is shown applied in several areas.